Scottish Gravers of Flint and Other Stones (Proceedings of the Society of Antiquaries of Scotland, 1938)
Gravers were common during the Upper Paleolithic and continued to be used in degenerate form in the Mesolithic. The essential characteristic of the graver is the chisel-edge formed by the meeting of two bezels, single or multi-faceted, at the extremity of a flake or blade, or sometimes of a core lending itself to suitable treatment. Most Scottish examples have been found in Tweedside.